Narrative of the life of Frederick Douglass, an American slave - Douglass, Frederick (Dover publications, 1995)
Originally published: Narrative of the life of Frederick Douglass, an American slave. Boston : Anti-Slavery Office, 1845.; Perhaps the most powerful and influential black American of his time, Frederick Douglass, cmbodied the tumultuous social changes that transfored the united States during the nineteenth century. In a career of unprecedented breadth, Douglass rose from the oppression of his slave's birth to fame for Abolitionist.